QUO VADIS KEPASTIAN HUKUM, HAK MENCALONKAN DIRI BAGI MANTAN NARAPIDANA KORUPSI DAN PENGURUS PARPOL DALAM PEMILU 2019 - Rikson H Nababan (Bawaslu Provinsi Kepulauan Riau, 2019)
The right to be nominated in an election is the political civil rights of every individual. This right is a first generation right or alsocalled an innate right, whose existence is automatically present when the individual is born, without having to first, be given by the state. Therefore, it has become an obligation for the state and state administrators, to provide protection for the fulfillment of these civil political rights and not to eliminate them for any reason. Likewise related to restrictions on these rights, must be regulated in a provision of the Act, with the aim of respecting the civil political rights of other citizens and creating order and order